Analysis of the Level of Resilience of Urban Communities in the Face of Flood Disasters in Bendungan Hilir Village - Muhammad Alfarizy Darmawan; Evan Mauro Aryandaru Anoi; Benediktis Daeli; rief Andyka Setiawan Tjenteng; Muhammad Fahrezy Putra Dwitama; Fathin Aulia Rahman (Institut Agama Islam Sunan Giri Ponorogo, 2026)
Floods are hydrometeorological disasters that often occur in urban areas and have an impact on social, economic, environmental, and public health aspects. Bendungan Hilir Village, Central Jakarta, is an area that still faces flood risk due to population density, regional characteristics, and limited infiltration areas. This study aims to analyze the level of community resilience to floods using the Sustainable Livelihood Framework (SLF) approach which includes human capital, natural capital, financial capital, physical capital, and social capital. The study used a quantitative approach with a survey method of 50 respondents selected by purposive sampling. Data was collected through questionnaires, interviews, observations, documentation, and spatial analysis using InaRISK BNPB's data processed with ArcGIS. The results of the study show that the community has good resilience in terms of drainage conditions, environmental cleanliness, waste management, house conditions, and road access. However, weaknesses are still found in disaster training, community skills, green open spaces, access to assistance, emergency funds, clean water, and income diversification, so that capacity building, green infrastructure, economic empowerment, and disaster institutions are needed